Behavior of Retail Gasoline Prices in the Philippines to Changes in Crude Oil Prices: Is it Symmetric or Asymmetric? - Kim, Jaewook (Philippine Management Review; Vol 19 (2012), 2012)
This study examines if the relationship between the behavior of retail gasoline prices in the Philippines and changes in world crude oil prices is indeed asymmetric or possibly symmetric. Based on weekly data from October 2005 to September 2010, test results reveal that there is no pattern symmetry between movements in retail gasoline prices and changes in crude oil prices. But there is amount symmetry in the responsiveness of unleaded retail gasoline prices changes to crude oil prices.
Keywords: Crude Oil; Retail Gasoline; Asymmetry; Symmetry